A Taxonomy of Game Balancing Elements - Parreiras, Marcus; Marques, Pedro; Xexéo, Geraldo (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
This study constructs a comprehensive taxonomy of game balancing elements using the Grounded Theory methodology. The taxonomy aims to aid game developers in understanding the factors influencing game balance, thereby informing design decisions. The research contributes to game studies by providing a theoretical foundation for further exploration and has potential implications for the development of industry guidelines and best practices.